Professor Girey Alievich Bairov (1922–1999) (to the 100th anniversary of the birth) - A. A. Kurygin; T. K. Nemilova; V. S. Dovganiuk (Вестник хирургии имени И.И. Грекова)
An outstanding Soviet and Russian pediatrician and pediatric surgeon, one of the founders of pediatric surgery in the USSR and the founder of the Leningrad Scientific School of Pediatric Surgeons, Doctor of Medical Sciences (1960), Corresponding Member of the USSR Academy of Medical Sciences (1963) and RAMS (1992), laureate of the USSR State Prize (1979), Honored Doctor and Honored Scientist of the RSFSR (1994), Professor (1962) Girey Alievich Bairov was born on May 2, 1922 in Alushta. In 1955, G. A. Bairov was the first in the Soviet Union to successfully operate on a newborn boy with esophageal atresia and tracheoesophageal fistula. In 1959, he was elected head of the Department of Pediatric Surgery with Orthopedics and Anesthesiology at the Leningrad Pediatric Medical Institute. In 1960, he defended his doctoral dissertation on the topic: «Fractures in the elbow joint in children». G. A. Bairov was a very versatile surgeon: he perfectly operated on newborns, children of different ages with various diseases of the chest and abdomen, performed urological, traumatological and orthopedic interventions, operated on the spine. In 1963, for outstanding achievements in the development of pediatric surgery, he was elected a corresponding member of the USSR Academy of Medical Sciences. For the development of methods of surgical treatment of congenital and acquired diseases of young children, he was awarded the State Prize of the USSR in 1979. G. A.Bairov was the author and co-author of about 400 scientific papers, including 20 monographs and textbooks, more than 40 inventions, rationalization proposals, new methods of surgical interventions. Under his direct supervision, 31 doctoral and 120 master’s theses were defended. Professor G. A. Bairov passed away on July 6, 1999 and was buried at the Smolensky cemetery in St. Petersburg.